Intestinal ischemia–reperfusion and blood–brain barrier compromise: pathways to cognitive dysfunction - Hammed, Opeyemi; Afolabi, Oladele; Ajike, Richard; Hezekiah, Oluwaseun; Alabi, Babatunde; Ajao, David; Saka, Waidi; Oyekunle, Olubunmi; Olusola, Bamidele (Frontiers in Neuroscience, 2025)
Intestinal ischemia–reperfusion (I/R) injury, a disorder occurring from interruption of blood flow to the intestines followed by its restoration, causes a cascade of events leading to systemic consequences, including cognitive impairment. This study analyses the complicated link between intestinal I/R damage and blood–brain barrier (BBB) compromise, highlighting essential processes such as systemic inflammation, gut microbiota dysbiosis, oxidative stress, vagus nerve activation, and altered gut microbial metabolite production. During I/R injury, the weakened gut barrier permits the translocation of microbial products and inflammatory mediators into the circulation, beginning systemic inflammation that disrupts the BBB and exacerbates neuronal damage. Furthermore, gut microbiota dysbiosis and altered gut microbial metabolite synthesis, such as short-chain fatty acids (SCFAs), can impact neuronal signaling and cognitive processes. By delineating these pathways, this study seeks to provide a comprehensive knowledge of the intricate interplay between intestinal I/R injury, BBB integrity, and cognitive function, opening the way for potential therapeutic approaches.